Coagulation Profile of Convalescent Plasma Donors and Recipients - Hanna H Pitkänen MD, PhD; Tuukka Helin MD, PhD; Tamim Khawaja MD; Jukka-Pekka Pietilä MD; Mikael Kajova MD; Hanna Välimaa MD, PhD, DDS; Tero Vahlberg MSc; Jarkko Ihalainen MD; Antti Vierikko MD; Olli Vapalahti MD, PhD; Anu Kantele MD, PhD; Riitta Lassila MD, PhD (Clinical and Applied Thrombosis/Hemostasis)
Convalescent plasma (CP) therapy for COVID-19 infection may have favorable safety but varying efficacy, with concerns about its procoagulant impact. We investigated whether administration of CP to hospitalized patients affects their coagulation profile. Fifty-four patients randomized in a double-blinded fashion received either placebo, low-titer CP (LCP) or high-titer CP (HCP). Donor blood samples were obtained at the time of the plasmapheresis, while recipient blood samples were collected before infusion, one day post-infusion and between two and six days after infusion. Routine laboratory follow-up, coagulation biomarkers, antiphospholipid antibodies, and thrombin generation (TG) were assessed. CP donors had normal blood cell counts and coagulation profiles, without differences between LCP and HCP donors at the baseline. All CP recipients were on low-molecular-weight heparin thromboprophylaxis at the time of the infusion. Despite randomization, the HCP group had lower baseline (p = 0.004) and Day 1 platelet counts (p = 0.019) than the LCP group. Von Willebrand antigen (VWF:Ag) levels clearly exceeded normal without differences at baseline. At Day 1, LCP recipients had higher VWF:Ag (mean ± SD 224 ± 15%) than HCP recipients (210 ± 8%) (p = 0.012). In all groups, overall 80% lupus anticoagulant was positive. Baseline TG variables were comparable, but again LCP recipients exhibited higher endogenous thrombin potential (ETP) (1313 ± 535 nM.min) (p = 0.038) and peak TG (184 ± 106 nM) (p = 0.037) than the HCP group (870 ± 425 nM.min and 86 ± 54 nM). Our findings show that LCP increases VWF:Ag levels and enhances TG despite the thromboprophylaxis. These results suggest that HCP induces less hypercoagulability than LCP, which may contribute to the variability in CP efficacy.